ANALISIS YURIDIS GUGATAN UNI EROPA KE WORLD TRADE ORGANIZATION TERHADAP INDONESIA AKIBAT REGULASI DAN KEBIJAKAN PEMBATASAN EKSPOR BIJIH NIKEL - Mulia Putra, Gede Rafael Julian; Greacy Geovanie, David (SETARA : Jurnal Ilmu Hukum, 2024)
The importance of regulations and policies issued by the Indonesian government, namely restrictions and prohibitions on the export of nickel ore. The purpose of this research is (1) to find out and analyze the form of the European Union's lawsuit against the WTO against Indonesia due to restrictions on exports of low grade nickel ore. (2) To analyze and identify the implications of the European Union's lawsuit against the WTO on legal and economic aspects resulting from restrictions on nickel ore exports. The type of research used in this research method is normative juridical research. By using a statutory approach and a case approach. The sources of legal materials used are legal materials consisting of primary legal materials and secondary legal materials. The research results obtained are (1) The Indonesian government implemented a policy of limiting nickel exports for various reasons, including increasing the added value of nickel mining, protecting natural resources, and diversifying the economy. This decision is also related to efforts to maintain international trade balance and encourage more environmentally friendly mining practices. (2) The nickel export ban imposed by the Indonesian government has had a major impact on trade relations between Indonesia and the European Union. The European Union, the world's largest consumer of nickel ore, has taken legal action and filed a lawsuit against Indonesia at the World Trade Organization (WTO). This incident has created tensions in trade relations and the resolution depends on the WTO decision.